2011
DOI: 10.1007/s00421-011-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

Maximal voluntary contraction force, SR function and glycogen resynthesis during the first 72 h after a high-level competitive soccer game

Abstract: The aim of this study was to examine maximal voluntary knee-extensor contraction force (MVC force), sarcoplasmic reticulum (SR) function and muscle glycogen levels in the days after a high-level soccer game when players ingested an optimised diet. Seven high-level male soccer players had a vastus lateralis muscle biopsy and a blood sample collected in a control situation and at 0, 24, 48 and 72 h after a competitive soccer game. MVC force, SR function, muscle glycogen, muscle soreness and plasma myoglobin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 43 publications
9
92
0
2
Order By: Relevance
“…Causes behind the increased oxygen consumption are not easy to determine, yet the re-synthesis of glycogen storages could be a possible explanation. The replenishment of glycogen has been shown to require up to 48 hours (46), and present blood lactate findings support this, as blood lactate level was still substantially lower under the 24-hour post-match test compared to the pre-match test. A reduced aerobic metabolic efficiency could thus be assumed to be the cause behind the findings of elevated oxygen in the recovery test.…”
Section: The Recovery Testsupporting
confidence: 73%
“…Causes behind the increased oxygen consumption are not easy to determine, yet the re-synthesis of glycogen storages could be a possible explanation. The replenishment of glycogen has been shown to require up to 48 hours (46), and present blood lactate findings support this, as blood lactate level was still substantially lower under the 24-hour post-match test compared to the pre-match test. A reduced aerobic metabolic efficiency could thus be assumed to be the cause behind the findings of elevated oxygen in the recovery test.…”
Section: The Recovery Testsupporting
confidence: 73%
“…Hence, both muscle glycogen and SR Ca 2+ release rate remained depressed in the H 2 O group whereas muscle glycogen and SR Ca 2+ release were significantly elevated in the CHO group in comparison to the Post measurement. (10,26) and unaltered (19,33) following exercise. These discrepancies in research may be related to the exercise mode and training status of individuals.…”
Section: Figure 1 and 2 Near Herementioning
confidence: 93%
“…An earlier review of 23 peer-reviewed papers, 11 of which were studies on recovery from running, also found insignificant effects from CG [39]. The mechanisms by which load bearing exercise retards recovery are complex and varied, and include muscle damage and the depletion of endogenous energy substrates [77], the accumulation of metabolic by-products [78,79] and impaired neuromuscular function [80]. It is therefore unsurprising that ameliorating muscle damage alone is often insufficient to aid recovery from running [33,81], as this milieu of degenerative processes is unlikely to be wholly addressed by a single recovery method.…”
Section: Compression Power Recovery and Runningmentioning
confidence: 99%